Leadership in Business Organizations: Concepts, Processes, and Strategies in Directing Organizations - Evi Novita Sari; Najwa Raisya Salsabila Azzahra; Nikmatul Khofifah; Ucik Sinta Nuriya; Nunuk Indarti (International Journal of Technology and Education Research, 2026)
Leadership is a strategic element in a business organization that plays a role in determining the direction, stability, and ability of the organization in dealing with environmental dynamics. This article comprehensively discusses the concept of leadership, including the definition, roles, and characteristics of an effective leader in the context of modern business. In addition, this article outlines the leadership process which includes vision formation, decision-making, communication, team coordination, and organizational change management. Leadership strategies are also the main focus, especially transformational, transactional, and situational styles that can be used to direct the organization according to the needs and challenges faced. The discussion shows that the effectiveness of leadership does not only depend on the individual qualities of the leader, but also on the ability to implement the right processes and strategies according to the internal and external conditions of the organization. Thus, this article provides a comprehensive understanding of how directed and adaptive leadership can improve the performance, competitiveness, and sustainability of business organizations in an ever-changing era.